PIP3 abundance overcomes PI3K signaling selectivity in invadopodia. Issue 4 (12th January 2022) - Jakubik, Charles T.; Weckerly, Claire C.; Hammond, Gerald R.V.; Bresnick, Anne R.; Backer, Jonathan M.
Abstract : PI3Kβ is required for invadopodia‐mediated matrix degradation by breast cancer cells. Invadopodia maturation requires GPCR activation of PI3Kβ and its coupling to SHIP2 to produce PI(3, 4)P2 . We now test whether selectivity for PI3Kβ is preserved under conditions of mutational increases in PI3K activity. In breast cancer cells where PI3Kβ is inhibited, short‐chain diC8‐PIP3  rescues gelatin degradation in a SHIP2‐dependent manner; rescue by diC8‐PI(3, 4)P2  is SHIP2‐independent. Surprisingly, the expression of either activated PI3Kβ or PI3Kα mutants rescued the effects of PI3Kβ inhibition. In both cases, gelatin degradation was SHIP2‐dependent. These data confirm the requirement for PIP3 conversion to PI(3, 4)P2 for invadopodia function and suggest that selectivity for distinct PI3K isotypes may be obviated by mutational activation of the PI3K pathway. Abstract : GPCR activation of PI3Kβ drives invadopodia‐mediated matrix degradation by breast cancer cells, via PI3Kβ coupling to SHIP2 to produce PI(3, 4)P2 . Surprisingly, expression of either activated PI3Kβ or PI3Kα rescues the effects of pertussis toxin or TGX221, which inhibit PI3Kβ. In both cases, matrix degradation is SHIP2‐dependent. Thus, selectivity for PI3K isotypes is obviated by mutational activation of PI3K signaling.